2011
DOI: 10.1135/cccc2011078
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox catalysis by [Ru(bpy)3]2+ to trigger transformations of organic molecules. Organic synthesis using visible-light photocatalysis and its 20th century roots

Abstract: Reactions triggered by light constitute a treasure trove of unique synthetic methods that are available to chemists. Photoinduced redox processes using visible light in conjunction with sensitizing dyes offer a great variety of catalytic transformations useful in the realm of organic synthesis. The recent literature amply shows that this preparative toolbox is expanding substantially. This review discusses historical and contemporary work in the area of photoredox catalysis with [Ru(bpy)3]2+. Elegant examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(109 citation statements)
references
References 146 publications
1
99
1
5
Order By: Relevance
“…The photocatalysts are mainly based on ruthenium or iridium thanks to their intense visible light absorption, long lived excited states and suitable redox potentials. Thus they can work through either an oxidation or a reduction cycle to produce reactive species, e.g., radicals or cations [112][113][114]116,[119][120][121][122][123][124]. Several ruthenium or iridium complexes have been introduced into the photoinitiating systems in the polymer photochemistry field (see Table 2).…”
Section: Ruthenium or Iridium Complexes Based Photoinitiating Systemsmentioning
confidence: 99%
“…The photocatalysts are mainly based on ruthenium or iridium thanks to their intense visible light absorption, long lived excited states and suitable redox potentials. Thus they can work through either an oxidation or a reduction cycle to produce reactive species, e.g., radicals or cations [112][113][114]116,[119][120][121][122][123][124]. Several ruthenium or iridium complexes have been introduced into the photoinitiating systems in the polymer photochemistry field (see Table 2).…”
Section: Ruthenium or Iridium Complexes Based Photoinitiating Systemsmentioning
confidence: 99%
“…13 In this context, we have recently demonstrated that photoredox catalysis can be employed to mediate the α-arylation of amines using electron-deficient benzonitrile coupling partners. 14 In this protocol, activation of the amine α-C–H bond is achieved via single-electron oxidation followed by α-deprotonation to generate the critical α-amino radical 1 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these results, the following mechanism is proposed: After excitation of the photocatalyst by blue . [40] The oxidant is reduced to sulfate and a sulfate radical anion that is capable of accepting an additional electron. [41] Regeneration of the photocatalyst is achieved by oxidizing TEMPO (2) to corresponding oxoammonium ion 2Ј.…”
Section: Resultsmentioning
confidence: 99%